2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20184470
|View full text |Cite
|
Sign up to set email alerts
|

Iron-deficiency and pruritus: a possible explanation of their relationship

Abstract: <p class="abstract">Pruritus of unknown origin is defined as itching lasting for more than 3 weeks without a clear identifiable cause. Aetiology of itching is wide ranging and includes chronic renal failure, cholestasis and internal malignancy. Iron deficiency has been described to be causative of pruritus but the mechanism underlying this association remains unclear. We report the case of a female patient with iron deficiency anemia and generalized pruritus, resolved after intravenous administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Therefore, we speculate that higher activity status and subsequent exposure to UV might predispose to rosacea and concurrently decrease the probability of CI occurrence. Higher haemoglobin concentration might also be associated with lower risk of pruritus; conversely, the role of anaemia in eliciting pruritus is widely acknowledged (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that higher activity status and subsequent exposure to UV might predispose to rosacea and concurrently decrease the probability of CI occurrence. Higher haemoglobin concentration might also be associated with lower risk of pruritus; conversely, the role of anaemia in eliciting pruritus is widely acknowledged (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…18 Pruritus with systemic causes constituted 29.8% of our patients. 19 Reported that 14-50% of pruritic adult and elderly patients without a clear dermatologic cause have an underlying internal cause for their symptom. 19 Renal diseases were the most common systemic cause of pruritus in elderly in the present study affecting 46.2% of the cases, as there was statistically significant difference between both groups regarding creatinine level (p value =0.012), which was not in agreement with 9 who found that kidney diseases represent only 9.7% of systemic causes of pruritus in elderly, but in line with our study 20 reported that renal pruritus was the most common systemic cause of pruritus and it affects 50-90% of patients undergoing peritoneal dialysis or hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases reports also added to the evidence that Pruritis can be seen in patients with iron de iciency anaemia. This condition can be explained as the normal assembly of dermal elastic ibres is negatively affected by the decreased serum iron level, which engenders the loss/reduced skin elasticity (Tammaro et al, 2018). Discussion with the treating physician, Pruritis was con irmed.…”
Section: Case Descriptionmentioning
confidence: 98%